Three Decades in Econophysics—From Microscopic Modelling to Macroscopic Complexity and Back - Alex Smolyak; Shlomo Havlin (Entropy, 2022)
We explore recent contributions to research in Econophysics, switching between Macroscopic complexity and microscopic modelling, showing how each leads to the other and detailing the everyday applicability of both approaches and the tools they help develop. Over the past decades, the world underwent several major crises, leading to significant increase in interdependence and, thus, complexity. We show here that from the perspective of network science, these processes become more understandable and, to some extent, also controllable.